Geochemical measurements of Holocene sediment sequence retrieved from Lake Loitsana, Finland - Shyhrete Shala; Karin Helmens; Stefan Engels; Peter Kuhry; Malin E Kylander; Tomi P Luoto; Sakari Salonen; Minna Väliranta; Jan Weckström (PANGAEA, 2025)
This dataset provides geochemical measurements for the Holocene sediment sequence retrieved from Lake Loitsana (Finland) in 2008. The data are presented as percentages (Corg, N), extperthousand vs PDB (δ13Corg) and extperthousand vs air (δ18O). All parameters are presented against both depth (cm) and age (cal yr. BP). Two age/depths models are presented: the first model represents the original age/depth model applied to the records (Shala et al., 2014; 2017) and the second age/depth model, which is the author-preferred version, presents updated age-estimates derived using the r package extquotesingleBacon extquotesingle (Blaauw and Christensen, 2011). The geochemical dataset provides information on Holocene lake ecosystem and catchment dynamics. A total of 144 samples from the Holocene sediment sequence were freeze-dried, ground and weighed into tin capsules for C/N-analysis. Additional material was taken from each sample for organic carbon (Corg) analysis. The material was weighed into silver capsules, treated with HCL (10%) and dried overnight before analysis. Concentrations were measured through combustion in a Carlo Erba NC2500 Elemental Analyzer at the Stable Isotope Lab at the Department of Geological Sciences, Stockholm University.